Cross-cultural bases of tendencies of civilization development - Vorobyova, Svetlana V.; Liahchylin, Anatolii A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The main trends in the reconstruction of cross-cultural bases of tendencies of civilizational development aresystematized. The methodological significance of the cultural-centric paradigm and the duality principle is revealed. The conditions of cross-cultural modeling of civilizational identity in the context of ontological and epistemological orthogonal factors are determined. The specifics of constructive interpretations of the cultural continuum are explained. The ways of substantiating the formal properties of tendencies of civilizational development are outlined: the search for relevant conditions; differentiation of ontological situations as states and processes.
Keywords: cross-cultural grounds; cultural-centric paradigm; duality principle; civilizational identity; cultural continuum; constructive continuum; relevance; conditions; processes